2020
DOI: 10.1016/j.cplett.2019.137069
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically unstable 2–isocyanophenol isolated in cryogenic matrices: Vibrational excitation, conformational changes and spontaneous tunneling

Abstract: Monomers of 2-isocyanophenol were generated in low-temperature solid Ar and N2 matrices by UV-irradiation of benzoxazole and characterized by infrared (IR) spectroscopy.Near-IR narrowband excitation of the first OH-stretching overtone of 2-isocyanophenol isolated in an N2 matrix converted the most stable cis into the higher-energy trans conformer.Interconversions between these conformers also occurred when the sample was vibrationally excited by the full, or filtered, broadband light of the spectrometer source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

8
0

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 47 publications
11
44
0
Order By: Relevance
“…Concomitantly, various new bands were observed in the IR spectrum registered after the irradiation. Owing to the good correspondence between the IR spectrum of the emerging photoproduct and that simulated for 2-isocyanophenol, these bands were reliably assigned to 4, as shown in Figure 1 quickly relaxes into the most stable cis form by means of H-atom quantum mechanical tunnelling, 27 following the same behavior previously reported for the other 2-substituted phenols isolated in solid Ar. 28−30 Consequently, all the observed bands of 4 are due to the most stable cis conformer.…”
Section: Photochemistry Of Matrix-isolated Benzoxazolesupporting
confidence: 71%
“…Concomitantly, various new bands were observed in the IR spectrum registered after the irradiation. Owing to the good correspondence between the IR spectrum of the emerging photoproduct and that simulated for 2-isocyanophenol, these bands were reliably assigned to 4, as shown in Figure 1 quickly relaxes into the most stable cis form by means of H-atom quantum mechanical tunnelling, 27 following the same behavior previously reported for the other 2-substituted phenols isolated in solid Ar. 28−30 Consequently, all the observed bands of 4 are due to the most stable cis conformer.…”
Section: Photochemistry Of Matrix-isolated Benzoxazolesupporting
confidence: 71%
“…The energy barrier for both cc → tc and ct → tt rotamerizations was computed to be ∼16 kJ mol –1 . However, these rotamerizations involve only the movement of a light particle (H atom), and they can occur by means of quantum tunneling through the torsional barrier. For a relatively large number of compounds constituted by conformers differing from each other by 180° rotation of a OH group, including substituted phenols, and separated by torsional barriers (in the direction of conformational relaxation) of the same order as those here computed for the cis-to-trans OH rotamerization, the less stable conformers have an extremely short lifetime because of their fast tunneling conversion into the most stable forms.…”
Section: Resultsmentioning
confidence: 58%
“…This led us to perform an experiment where the sample was exposed to broadband IR-radiation emitted from a kanthal wire electrically heated to a reddish-orange glow. The idea was to excite vibrationally the matrix-isolated molecule above the barrier for conformational interconversion (∼10 kJ mol –1 , see Figure S2) in order to induce changes in the relative populations of the two conformers, thus facilitating their spectroscopic identification. ,, The IR-induced spectral changes are reflected in the difference spectrum presented in Figure a. As one can see, one set of the existing bands (or band components) increases their intensity (3637, 1278/1273, 1227, 1173, 1113/1110/1107, 1055, 996/994, and 944 cm –1 , marked with red circles), while another set of bands (or band components) decreases their intensity (3643, 1259, 1222, 1179, 1168, 1117, 1065, 997, and 938 cm –1 , marked with blue squares).…”
Section: Resultsmentioning
confidence: 99%
“…Since then, small aliphatic carboxylic acids (e.g., acetic and propionic acid) have served as prototype molecules to better understand conformational dynamics. , Nowadays, it is well established that the higher-energy trans -COOH moiety (OC–O–H dihedral angle near 180°) can be produced from its corresponding cis analogue. , However, capture of trans -forms remains challenging, as they tend to spontaneously relax back to their more stable cis counterparts by H-atom quantum tunneling . In an elegant approach, Khriachtchev et al demonstrated that trapping the trans -forms in solid N 2 , instead of the more conventional noble gases (Ar, Kr, and Xe), enhances the stability of these conformations. , Using this approach, several high-energy species containing a trans -OH group were stabilized and characterized by stationary spectroscopic techniques, which otherwise would not have been possible. , …”
Section: Introductionmentioning
confidence: 99%
“…9,10 Using this approach, several high-energy species containing a trans-OH group were stabilized and characterized by stationary spectroscopic techniques, which otherwise would not have been possible. 11,12 Recently, the studies of small prototype carboxylic acids were extended to larger α-substituted aromatic acids. In most aliphatic carboxylic acids the cis orientation of the COOH moiety is the most stable form by more than 15 kJ mol −1 .…”
Section: Introductionmentioning
confidence: 99%